"Pochwały przyjaciółki", czyli o rozterkach leksykalnych tłumacza "Pieśni z Ripoll" - Grzelak-Krzymianowska, Adriana; Woźniak, Maria Judyta; Agnieszka Gralak (Rome and Iberia : Inspirations and Connections throughout History, 2021)
Carmina Rivipullensia is the only existing collection of medieval Latin lyrical love poetry deriving from Spain. It is a unique testimony to the skilful and creative use of the Latin poetic tradition on the Iberian Peninsula. The whole collection which is little-known in Poland has not yet been translated into Polish. The aim of this chapter is to present a proposed translation of one of the poems, Laudes amice, with a commentary on the literary devices applied in the translation, as well as dilemmas faced by a contemporary translator.